The effects of job security on employee performance: a case study of First Banking Corporation (FBC Bank Limited). - Kutesera, Loreen (Midlands State University, 2019)
The purpose of the study was to assess the effects of job security on employee performance at First Banking Corporation Limited (FBC Bank Ltd). This was in light of the underperforming Zimbabwean economy and the subsequent tremors in the banking sector. Tremors such as the liquidity crisis which has led to the promotion of the use of ‘plastic money’, mobile and ebanking, and the dwindling clientele for the banks have led to banks revise the nature of work and adopt survival strategies to cut costs. The research was aimed at assessing the effects of job security on employee performance in such an environment. All respondents who were selected were on permanent contracts. Contractual employees were excluded from the study as already they have no job security. The researcher applied qualitative research methodology and a case study approach was adopted. The population for the study was 390. The sample size was 40 respondents who were selected using the purposive and convenience sampling techniques. The sample was made up of 5 managerial and 35 non-managerial staff. The response rate was 37 out of 40 i.e. 93%... The research findings are presented in the form of tables, themes and narratives and extracts from the interviews. Overall findings of the research concurred with literature that economic downturn had a formidable effect on job security among other factors, as it resulted in job insecurity since organisation were forced by the macro-environment to cut costs by resorting to new forms of employment. Job security was found to be the prominent factor affecting employee performance at FBC Bank Ltd, as employees were demotivated by low levels of security which they felt was a breach to the psychological contract. Research findings also showed that low levels of job security were also a reason for employee mobility within the banking sector. The study found out that the performance of the Zimbabwean economy posed the greatest challenge to ensuring job security in FBC Bank Ltd. The researcher concluded that high levels of jobs security had a positive effect on employee performance whereas low levels had a negative effect on employee performance. The researcher recommended that the organisation builds a relationship based on trust with employees by effectively communicating its position and future plans so as to allay employee fears. The researcher recommended that future research needs to be carried out to assess the effects of technological advancements and the new forms of banking on the job security of bank employees in Zimbabwe.